Performance improvement of a transmission synchronizer via sensitivity analysis and Pareto optimization. Issue 1 (1st January 2018) - Irfan, Muhammad; Berbyuk, Viktor; Johansson, Håkan
Abstract: Gear-shifting mechanism has a key role in transmission system of a vehicle. During gear shifting, there is a risk of losing the engine optimal speed that will ultimately lead to more emission from the vehicle. It is demanded for optimal performance of transmission systems to increase quality of synchronizer used for gear shifting. Especially in the case of heavy vehicles, the synchronizer performance needs to be robust more even during different operating scenarios. Synchronization process varies by changing its parameters values. So one of the ways to improve performance of the synchronizer is to optimizing its parameters. In the paper, a generic synchronizer mechanism (GSM) is considered. Mathematical model of GSM is presented based on constrained Lagrangian formalism (CLF) and detailed kinematics of synchronization process in transmission system. Speed difference at the end of the main synchronization phase and synchronization time are chosen as two objectives. The following eight parameters of the synchronizer have taken as input parameters: cone angle, cone coefficient of friction, cone radius, rate of shift force, blocker angle, blocker coefficient of friction, gear moment of inertia, and ring moment of inertia. Influence of the parameters on objectives is studied. The values of the objective functions decrease with increasing some of the parameters and increase with increasing others. Not only the objective functions have opposite behavior between the parameters but also have opposite behavior with variation of the same parameters. For example, the synchronization time decreases but the speed difference increases with increasing cone coefficient of friction. The Matlab routine of multi-objective optimization is applied to obtain the optimized parameter values of the generic synchronizer at different operating conditions. In the first case, the sleeve is considered as a master, in the second case the gear is considered as master, and in the third case both sleeve and gear are considered as slaves. In each case, three different operating conditions are studied which are nominal, transmission vibrations, and road grade. The obtained results of biobjective optimization (Pareto fronts, Pareto sets, and corresponding performance diagrams) are analyzed and the most influencing synchronizer parameters have been identified.